2020
DOI: 10.1002/jssc.202000171
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile of fish species by liquid chromatography coupled to mass spectrometry and a novel linear retention index database

Abstract: In a previous article, Rigano et al. established a new linear retention index system for the identification of triacylglycerols by liquid chromatography methods only on the basis of the retention behavior and independently from many experimental parameters. In that work, a database of 209 compounds was built, but only 54 of them, typical of vegetable oils, were confirmed by mass spectrometry. The aim of the present research is to extend the applicability of the novel approach to more complex samples, such as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…A new software, namely ChromLinear (Chromaleont, Messina, Italy) version 1.0, developed ad hoc for LRI database handling in LC [ 60 ], was employed for a fast and automatic peak identification. The software is able to perform a dual-filter search, thus, excluding from the list of compounds with a high spectral similarity (minimum direct and reverse match were both set at a value of 800; they are calculated based on the NIST MS search algorithm), those falling out the window of ±4 LRI units.…”
Section: Methodsmentioning
confidence: 99%
“…A new software, namely ChromLinear (Chromaleont, Messina, Italy) version 1.0, developed ad hoc for LRI database handling in LC [ 60 ], was employed for a fast and automatic peak identification. The software is able to perform a dual-filter search, thus, excluding from the list of compounds with a high spectral similarity (minimum direct and reverse match were both set at a value of 800; they are calculated based on the NIST MS search algorithm), those falling out the window of ±4 LRI units.…”
Section: Methodsmentioning
confidence: 99%
“…The identification was primarily performed in an automatic way by using the novel ChromLinear software, which enables a fast data processing by matching with a previously built and constantly implemented LRI database [ 18 , 19 , 43 ] and home-made MS library reported in a previous work [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding lipid analysis, FAs are generally investigated, in form of FA methyl ester (FAME) derivatives, by gas chromatography (GC) coupled to flame ionization detection (FID) and mass spectrometry (MS), for quantitative and qualitative purposes, respectively [ 14 , 15 ]. Instead, reversed phase liquid chromatography (RP-LC) is the most suitable separation approach for complex lipid analysis, as in the case of TAGs [ 16 , 17 , 18 , 19 ]. In RP-LC, hydrophobic interactions between the target analytes and the stationary phase, normally a octadecylsilica (C18) particle packed column, provide a separation of the mixture that directly depends on the TAG partition number (PN), calculated from the equation PN = ECN = CN—2DB (equivalent carbon number, carbon chain length and double bonds number, respectively) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a contrasting body of research that has found EPA can increase with water contamination [ 91 ]. Thus, the explanation for the decline in EPA in silver carp from the leading edge relative to conspecifics from downstream is not fully understood, but may in part be due to the type of contaminant(s) to which organisms are exposed [ 91 ], or food available [ 92 ], and should be investigated in future work. Together, results from this study clearly show that silver carp at the leading edge of the Illinois River have reduced levels of EPA relative to the downstream core population, possibly indicative of increased energetic demands as a result of xenobiotic exposure, and further studies are needed explain the mechanism for this finding.…”
Section: Discussionmentioning
confidence: 99%